The Importance of Developing the Creative Activity of Future Primary Teachers - Egamova Zilola Ayubovna (Scientific Trends, 2025)
The article discusses the difficulties and problems that arise in preparing future primary school teachers for organizing creative activities, the difficulties they encounter in connection with the characteristics of the pedagogical personality, and strategies for overcoming difficulties that arise in the work of a teacher.
Keywords: Creativity, creativity, creative, reproductive activity, professional activity, professional development, psychological protection, professional deformation.